A DUPLICATION dup(4)(q28q35.2) DE NOVO IN A NEWBORN - Cernakova, Iveta; Kvasnicova, Marta; Lovasova, Zuzana; Badova, Nora; Drabek, Jiri; Bouchalova, Katerina; Trojanec, Radek; Hajduch, Marian (Biomedical papers, 2006)
We report here a case of a newborn with hypotrophy and somatic stigmatization: microcephaly, facial dysmorphism, heart defect and immunodeficiency syndrome. The proband's karyotype was 46,XY,dup(4)(q28q35.2) de novo with chromosomal breaks in 4% of metaphases. We demonstrate the usefulness of a combination of physical examination, classical cytogenetics, FISH and PCR techniques in order to establish correct diagnosis because of overlap of some clinical and cytogenetic features of Nijmegen breakage syndrome (NBS) and duplication 4q in our patient. Although FISH technique detected translocation t(14q;21q) in 4 metaphases, deletion 657del5 in exon 6 of the NBS1 gene associated with NBS in Slavic population was not confirmed. We compare in this report similarity of the clinical picture of our patient, NBS cases and other patients carrying a duplication of the distal part of 4q as described in the literature.
Keywords: Duplication 4q syndrome/Nijmegen breakage syndrome/Cytogenetics/G-band technique/Fluorescence in situ